Zinc Chloride Catalyzed Amino Claisen Rearrangement of 1-N-Allylindolines: An Expedient Protocol for the Synthesis of Functionalized 7-Allylindolines - Jain Seema (Heterocyclic Communications, 2019)
7-Allylindolines are valuable synthons for designing biologically active molecular libraries. Lewis acid catalyzed amino-Claisen rearrangement provides a one pot synthetic entry to these heteroarenes. In this context, Zinc chloride (ZnCl2)–N,N-dimethylformamide system efficiently catalyzed amino-Claisen rearrangements of 1-N-allylindolines to 7-allylindolines. The rearrangement is influenced by stereoelectronic effects of substituents present in 1-N-allylindolines. The substrates containing electron donating functionalities underwent rearrangement at lower temperature than substrates with electron withdrawing functional groups. The regioselectivity of the process is governed by the substitution pattern on allyl moiety in 1-N-allylindoline as well as ZnCl2 catalyst loading in the reaction system.